IMPLEMENTATION OF AN UNDERGRADUATE INTEGRATED BIOLOGY & CHEMISTRY (iBC) COURSE - Balansag, Jayson (PEOPLE: International Journal of Social Sciences, 2018)
An integrated biology and chemistry (iBC) course for freshmen college students was developed in University of Delaware. This course will prepare students to (1) become interdisciplinary thinkers in the field of biology and (2) collaboratively work with others from multiple disciplines in the future. This study documented and described the implementation of the course in terms of its physical environment, course format and scheduling, teaching team, and course content. The challenges in the implementation and how they were addressed were also described. The information gathered from reading literature, classroom observations, and interviews were used to carry out the purpose of this study. The course is taught in the Interdisciplinary Sciences Learning Laboratories of the university. The iBC is composed of lectures, laboratories, studio sessions, and workshops and is taught by the faculty from the biology and chemistry departments. In addition, the teaching team involved in the delivery of the course is composed of the preceptors, the graduate teaching assistants, and studio fellows who facilitate the laboratory and studio sessions. In addressing the challenge of integrating the topics in both disciplines, the topics and laboratory activities in both disciplines were aligned. The iBC can be used as a model for other higher education institutions who wish to implement an integrated biology course.